Characterisation and modelling of a fractured crystalline aquifer contaminated with hydrocarbons - Van Rooy, J.L. (Jan Louis) (University of Pretoria, 2013)
Dissertation (MSc (Engineering and Environmental Geology))--University of Pretoria, 2003.